ANALISIS MANAJEMEN SYARIAH DALAM PENGELOLAAN PERUSAHAAN DENGAN STRUKTUR KEPEMILIKAN OLEH KELUARGA DI CV SANTOSA - Fika Fitria Fitria Ningsih; Rully Trihantana; Ria Kusumaningrum (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
One of the businesses that is growing rapidly and has become one of the prominent businesses in Indonesia is the family business. CV Santosa, which is the object of this research, is a family business domiciled in Jakarta and owned by a non-Muslim family. There is a uniqueness in family companies where the majority of share ownership and management of the company are managed and owned directly by the family. In addition, the company has prioritized tolerance for Muslim employees. By allowing employees to wear headscarves, perform prayers, and provide a prayer room. However, in managing a company, a professional management system is needed, this can be applied to the principles of Good Corporate Governance which become a guideline for good corporate governance, including the principles of Transparency, Accountability, Responsibility, Independence, and Fairness. Islam has a more complete concept, with the concepts of akhlakul karimah and piety to Allah Subhanahu Wa Ta'ala which are the basic beliefs to avoid practices that break the law and are dishonest in accepting the Trust. This study aims to analyze sharia management practices of company management with a family ownership structure so that the company can be sustainable. The type of method used in this research is descriptive qualitative. The results in this study show that the two most important values ​​that are in line as the basis for realizing ethical corporate governance at CV Santosa are the values ​​of 'adl (justice) and the values ​​of nubuwwah (prophecy) where the Prophet Muhammad Sholallahu Alaihi Wassalam has a great nature. namely: sidiq (behaving honestly and correctly), amanah (trustworthy & responsible), tabligh (delivering and being open/transparent) and fathonah (smart). That in business the level of fairness, honesty, responsibility, transparency is very important.